2017
DOI: 10.3389/fnmol.2017.00372
|View full text |Cite|
|
Sign up to set email alerts
|

Dusp16 Deficiency Causes Congenital Obstructive Hydrocephalus and Brain Overgrowth by Expansion of the Neural Progenitor Pool

Abstract: Hydrocephalus can occur in children alone or in combination with other neurodevelopmental disorders that are often associated with brain overgrowth. Despite the severity of these disorders, the molecular and cellular mechanisms underlying these pathologies and their comorbidity are poorly understood. Here, we studied the consequences of genetically inactivating in mice dual-specificity phosphatase 16 (Dusp16), which is known to negatively regulate mitogen-activated protein kinases (MAPKs) and which has never p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
4
11
0
Order By: Relevance
“…This was secondary to blockage of the midbrain aqueduct by the expansion of neural progenitor cells, eventually preventing the outflow of cerebrospinal fluid. Interestingly only an increase in cells staining positively for phospho-p38 was observed in the affected regions of the CNS indicating that this MAPK, rather than ERK or JNK could be the relevant target [ 199 ].…”
Section: The Jnk and P38 Specific Mkpsmentioning
confidence: 99%
“…This was secondary to blockage of the midbrain aqueduct by the expansion of neural progenitor cells, eventually preventing the outflow of cerebrospinal fluid. Interestingly only an increase in cells staining positively for phospho-p38 was observed in the affected regions of the CNS indicating that this MAPK, rather than ERK or JNK could be the relevant target [ 199 ].…”
Section: The Jnk and P38 Specific Mkpsmentioning
confidence: 99%
“…Indeed, WES revealed an additional de novo frameshift variant in the DUSP16 gene in the index patient, who also showed additional somatic features, anxiety disorder, and psychiatric episodes at very young age. A recent study reported that Dusp16 plays a critical role in neurogenesis by balancing neural progenitor cell proliferation and neural differentiation (Zega et al, ). Moreover, mouse mutants lacking a functional Dusp16 gene developed fully‐penetrant congenital obstructive hydrocephalus together with brain overgrowth (Zega et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that Dusp16 plays a critical role in neurogenesis by balancing neural progenitor cell proliferation and neural differentiation (Zega et al, ). Moreover, mouse mutants lacking a functional Dusp16 gene developed fully‐penetrant congenital obstructive hydrocephalus together with brain overgrowth (Zega et al, ). When focusing on common genetic variants, we also found nominally significant association of DUSP16 with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…On PND 28, the pups were weaned and housed with same sex littermates. Genotype was confirmed by PCR using a tail snip from the dams and sires before breeding as previously described [52].…”
Section: Mouse Breedingmentioning
confidence: 99%